A robust approach for trajectory tracking control of a quadrotor with experimental validation. (November 2016) - Pérez-Alcocer, Ricardo; Moreno-Valenzuela, Javier; Miranda-Colorado, Roger
Abstract: In this paper, a new control scheme for motion control of quadrotors is presented. The proposed model based controller makes use of simple estimations of vehicle parameters. Besides, the controller is developed under properties of the vehicle model. A rigorous analysis is developed to prove that the closed-loop system trajectories are uniformly ultimately bounded. The validity of the proposed control scheme is tested by numerical simulations and experimental results. This validation shows that the proposed controller guarantees that the quadrotor performs tracking of a desired pose (position and orientation) trajectory with good accuracy. The new scheme has been compared with respect to other robust controllers. The results indicate better tracking accuracy for the new scheme. Abstract : Highlights: A new robust motion controller for quadrotors is introduced. The new scheme is based on using only rough estimation of the quadrotor parameters. The new scheme ensures position and yaw angle error to be uniformly ultimately bounded. The new scheme is validated by numerical simulations and real experiments. A comparative analysis with respect to other robust approaches is given. The real time experiments are carried out in a Qball 2.